The Moderating Role of Personalization on Attitude-Emotion-Behavior (AEB) Model - Anggraini, Josephine Diah; Adiwijaya, Michael; Herjanto, Halimin (Indonesian Management and Accounting Research, 2024)
There is no doubt that push notifications have become an important business communication tool. This study investigates how smartphone users’ attitude toward push notifications affects their behavioral response. Based on Smart-PLS statistical results from a study of 100 Indonesian smartphone users, three important findings emerged. First, smartphone users’ attitude toward push notifications significantly and positively influences their emotional value. Second, emotional value strongly affects users’ behavioral response. Third, personalization moderates the relationship between attitude toward push notifications and emotional value and between emotional value and behavioral response. The findings of our study extend the current research repertoires on push notifications as well as offering a clear direction for future research and managerial suggestions.